Success Mantra for effective management with reference to Mahabharata - Kapil Tewari, Shreshthi Prakash (European Economic Letters (EEL), 2023)
The implementation of management concepts as revealed in our ancient knowledge and recorded in our sacred scriptures is the Indian Ethos for management. Indian Ethos for Management is the formal name for the body of knowledge that draws its conclusions from the vast and varied Indian system of ethics. Management requires cultural sensitivity since it is a behavioral science. The cultural foundation of India serves as the basis for Indian mythology for management, and as a nation whose culture has its origins in religion, it does take its teachings from the local faiths. One of the most important books in Indian history, the Mahabharata, may be used as a resource to acquire unique management lessons and get insight into diverse organizational working methods. This will help managers to run successful organizations.